2016
DOI: 10.1002/chem.201603607
|View full text |Cite
|
Sign up to set email alerts
|

A Multi‐responsive Regenerable Europium–Organic Framework Luminescent Sensor for Fe3+, CrVI Anions, and Picric Acid

Abstract: A novel luminescent microporous lanthanide metal-organic framework (Ln-MOF) based on a urea-containing ligand has been successfully assembled. Structural analysis revealed that the framework features two types of 1D channels, with urea N-H bonds projecting into the pores. Luminescence studies have revealed that the Ln-MOF exhibits high sensitivity, good selectivity, and a fast luminescence quenching response towards Fe , Cr anions, and picric acid. In particular, in the detection of Cr O and picric acid, the L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
90
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 254 publications
(90 citation statements)
references
References 176 publications
0
90
0
Order By: Relevance
“…The patterns in Figure S11 confirmed that the sample of NUM‐5 maintained the crystallinity after titration and cyclic experiments. Hence, the fluorescence intensity reduction was not due to the decomposition of crystalline structures . Then, we examined the filtrate of NUM‐5 with Cr VI (Cr 2 O 7 2− /CrO 4 2− ) in titration experiments by ICP analysis and solid‐state fluorescence spectra measurement.…”
Section: Stability Characterization Of Num‐5mentioning
confidence: 99%
See 1 more Smart Citation
“…The patterns in Figure S11 confirmed that the sample of NUM‐5 maintained the crystallinity after titration and cyclic experiments. Hence, the fluorescence intensity reduction was not due to the decomposition of crystalline structures . Then, we examined the filtrate of NUM‐5 with Cr VI (Cr 2 O 7 2− /CrO 4 2− ) in titration experiments by ICP analysis and solid‐state fluorescence spectra measurement.…”
Section: Stability Characterization Of Num‐5mentioning
confidence: 99%
“…Therefore, they are a good candidates for detecting Cr VI (Cr 2 O 7 2− /CrO 4 2− ) in aqueous solution . In this regard, some LMOF probes for Cr VI (Cr 2 O 7 2− /CrO 4 2− ) have been reported recently; however, the lack of water stability and recyclability impedes their applications in practice . Thus, the development of a new LMOF for sensing Cr VI (Cr 2 O 7 2− /CrO 4 2− ) in aqueous solution with high sensitivity, selectivity and excellent recyclability is extremely beneficial.…”
Section: Introductionmentioning
confidence: 99%
“…To further understand the results, the luminescence quenching efficiency can be calculated by using the Stern‐Volmer equation: I 0 /I = K sv [BZH] + 1, The Stern‐Volmer plots display an almost linear relationship for benzaldehyde, with the K sv values of 1.6073 × 10 4 (R 2 = 0.9964) and 8.1164 × 10 2 (R 2 = 0.9953) for 1 and 2 , respectively. Further detailed analysis denotes that the detection limits for benzaldehyde are 2.10 μM and 9.68 μM for 1 and 2 , respectively, according to 3 σ / k ( σ : standard error; k : slope), illustrating 1 and 2 had a sensitive quenching effect towards BZH (Figure c).…”
Section: Resultsmentioning
confidence: 97%
“…For example, grafting hydrogen bond donor functionality, such as amides (11)(12)(13)(14)(15)(16)(17)(18)(19)(20), ureas (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32), thioureas (33), and squaramides (34)(35)(36), (Figure 1(a)) onto the organic scaffold of the MOF can enhance properties including carbon dioxide capture (13,15,17,18), anion binding (20,21), sensing (28), and organocatalytic activity (6). Urea-functionalised MOFs in particular have been found to catalyse FriedelCrafts reactions between pyrroles and nitroalkenes (22,24,27,29,31), Henry reactions between aldehydes and nitromethane (23), and the methanolysis of epoxides (25).…”
Section: Crystallographymentioning
confidence: 99%